How effective is legal protection in Indonesia in handling investment fraud cases compared to other countries? - Oudy pajow, Roof; M Polontoh, Herry (Ipso Jure, 2024)
Legal protection for investors is crucial in preventing the negative impact of rampant investment fraud, especially in the digital era that facilitates access to information. The ever-growing phenomenon of investment fraud shows the importance of evaluating the effectiveness of existing legal frameworks. This study aims to analyze the effectiveness of legal protection in Indonesia in dealing with investment fraud cases, with a normative juridical approach that examines relevant regulations in Indonesia and compares them with other countries such as the United States and India. This method is used to understand the weaknesses and challenges in the implementation of existing laws. The results of the study show that although Indonesia has a comprehensive legal framework, such as Law Number 8 of 1995 on the Capital Market and the Electronic Information and Transaction Law (UU ITE), challenges in law enforcement and public education are still significant obstacles. Unlike the US and India, which implement strict sanctions and have strict supervision, legal protection in Indonesia still needs reforms to increase the deterrent effect for actors and strengthen public trust in the investment system.